A people power philosophy: republican ideology in opposition in Tanzania. Issue 3 (3rd April 2023) - Paget, Dan
ABSTRACT: This article is about democratic political thought and African political parties. Studies judge that opposition speak about democracy, but rarely express democratic ideologies. This determination arises from democracy's perceived hegemony. As democracy is accepted, opposition parties invoke democratic ideas without advocating them. I contest this line of argument. There are multiple visions of democracy. Therefore, whether or not democracy is hegemonic, not all arguments for and perspectives on it are. By omission, the literature on African parties has denied this variety in democratic thought and precluded the study of one variant of it in particular: republicanism. Republicanisms elevate domination and corruption as ills and advocate limiting state power and empowering citizens. I analyse the "people's power philosophy" of leading Tanzanian opposition party, Chadema. It imagines a ruling party oligarchy which pursues its private interests through an interconnected system of domination and corruption. Chadema advocates a new constitution to undo that system: institutional reforms that limit state power and empower citizens. It claims that it can do so by overpowering the oligarchy in a popular struggle. It imagines struggle as the breaking of everyday dominance and therefore as emancipatory: a second liberation. I argue that this philosophy constitutes a republican-democratic ideology.